Sensible Materials Mediatizations of Juvenile. Conflict based on literary works of Andres Caicedo - Valencia, Víctor (InMediaciones de la Comunicación, 2019)
This article focuses on how the youthful conflict has mutated among middle class youngsters in Cali (Colombia) from the arrival of the first analog devices to the massification of mobile devices and social media, and how the latest foster new spaces to meet, discuss and interact with other youngsters of similar ages and social stratification. This article is based on a case study conducted in Cali in 2015/2016, that took as starting point the narratives about the youthful conflict presented in some of Andrés Caicedo Estela’s literary work (1951/1977). A chatting took place with 93 young caleño readers of that author on how the new-growing mediatisation allows the handling of conflicts between old time and new young bourgeois, from a time considered on its way towards medialization to the current one that might be called trans-mediated. It is concluded that the main difference between the time narrated by Caicedo Estela and present time, lies on the fact that tactile touch screens work as expiatory temples to which a large part of today´s youngsters rely on in order to avoid the factual reality. They seem to be living in a kind of virtuality that confines them into a delayed present of superimposed realities.